Activation of spinal PDGFRβ in microglia promotes neuronal autophagy via p38 MAPK pathway in morphine‐tolerant rats. Issue 2 (2nd June 2021) - Jia, Xiaoqian; Zhang, Anqi; Li, Zheng; Peng, Xiaoling; Tian, Xuebi; Gao, Feng
Abstract: The adverse side effects of opioids, especially antinociceptive tolerance, limit their clinical application. A recent study reported that platelet‐derived growth factor receptor β (PDGFRβ) blockage selectively inhibited morphine tolerance. Autophagy has been reported to contribute to the cellular and behavioral responses to morphine. However, little is known about the relationship between PDGFRβ and autophagy in the mechanisms of morphine tolerance. In this study, rats were intrathecally administered with morphine twice daily for 7 days to induce antinociceptive tolerance, which was evaluated using a tail‐flick latency test. By administration autophagy inhibitor 3‐Methyladenine, PDGFRβ inhibitor imatinib, p38 mitogen‐activated protein kinase (MAPK) inhibitor SB203580 hydrochloride and minocycline hydrochloride, western blot, immunofluorescence, and transmission electron microscopy techniques were used to elucidate the roles of PDGFRβ, autophagy, and related signaling pathways in morphine tolerance. This study demonstrated for the first time that spinal PDGFRβ in microglia promotes autophagy in gamma‐aminobutyric acid (GABA) interneurons through activating p38 MAPK pathway during the development of morphine tolerance, which suggest a potential strategy for preventing the development of morphine tolerance clinically, thereby improving the use of opioids in pain management. Abstract : Morphine is the most effective and widely used drug for the management of pain. However, tolerance is a major limitation to its prolonged use in clinical practice. Autophagy has been reported to contribute to the cellular and behavioral responses to morphine. Meawhile, PDGFRβ blockage could selectively inhibit morphine tolerance. Given this situation, we try to explore the relationship between PDGFRβ and autophagy in morphine tolerance. We firstly report that activating PDGFRβ in spinal microglia can induce autophagy in GABAergic neurons via p38 MAPK pathway in morphine‐tolerant rats, which may be a novel therapeutic target for treatment of morphine tolerance. GABA, gamma‐aminobutyric acid; LC3, microtubule associated protein light chain 3; PDGFR, platelet‐derived growth factor receptor; p‐PDGFRβ, phosphorylated platelet‐derived growth factor receptor β; p‐p38, phosphorylated p38.